(untitled) - Ramage, John D. (Boston, 1996)
Solidly grounded in current theory and research, yet eminently practical and teachable, The Allyn & Bacon Guide to Writing has set the standard for first-year composition courses in writing, reading, critical thinking, and inquiry.
Keywords: English language,Anh ngữ thực hành; Rhetoric,Tu từ học